Indo-Anglian: Connotations and Denotations - Susheel Kumar Sharma (East European Journal of Psycholinguistics, 2018)
A different name than English literature, ‘Anglo-Indian Literature’, was given to the body of literature in English that emerged on account of the British interaction with India unlike the case with their interaction with America or Australia or New Zealand. Even the Indians’ contributions (translations as well as creative pieces in English) were classed under the caption ‘Anglo-Indian’ initially but later a different name, ‘Indo-Anglian’, was conceived for the growing variety and volume of writings in English by the Indians. However, unlike the former the latter has not found a favour with the compilers of English dictionaries. With the passage of time the fine line of demarcation drawn on the basis of subject matter and author’s point of view has disappeared and currently even Anglo-Indians’ writings are classed as ‘Indo-Anglian’. Besides contemplating on various connotations of the term ‘Indo-Anglian’ the article discusses the related issues such as: the etymology of the term, fixing the name of its coiner and the date of its first use. In contrast to the opinions of the historians and critics like K R S Iyengar, G P Sarma, M K Naik, Daniela Rogobete, Sachidananda Mohanty, Dilip Chatterjee and Gayatri Chakravorty Spivak it has been brought to light that the term ‘Indo-Anglian’ was first used in 1880 by James Payn to refer to the Indians’ writings in English rather pejoratively. However, Iyengar used it in a positive sense though he himself gave it up soon. The reasons for the wide acceptance of the term, sometimes also for the authors of the sub-continent, by the members of academia all over the world, despite its rejection by Sahitya Akademi (the national body of letters in India), have also been contemplated on. ReferencesAlphonso-Karkala, John B. (1970). Indo-English Literature in the Nineteenth Century, Mysore: Literary Half-yearly, University of Mysore, University of Mysore Press.Amanuddin, Syed. (2016 [1990]). “Don’t Call Me Indo-Anglian”. C. D. Narasimhaiah (Ed.), An Anthology of Commonwealth Poetry. Bengaluru: Trinity Press.B A (Compiler). (1883). Indo-Anglian Literature. Calcutta: Thacker, Spink and Co. PDF. Retrieved from: https://books.google.co.in/books?id=rByZ2RcSBTMC&pg=PA1&source= gbs_selected_pages&cad=3#v=onepage&q&f=false---. (1887). “Indo-Anglian Literature”. 2nd Issue. Calcutta: Thacker, Spink and Co. PDF. Retrieved from: http://www.jstor.org/stable/60238178Basham, A L. (1981[1954]). The Wonder That Was India: A Survey of the History and Culture of the Indian Sub-Continent before the Coming of the Muslims. Indian Rpt, Calcutta: Rupa. PDF. Retrieved from: https://archive.org/details/TheWonderThatWasIndiaByALBashamBhushan, V N. (1945). The Peacock Lute. Bomaby: Padma Publications Ltd.Bhushan, V N. (1945). The Moving Finger. Bomaby: Padma Publications Ltd.Boria, Cavellay. (1807). “Account of the Jains, Collected from a Priest of this Sect; at Mudgeri: Translated by Cavelly Boria, Brahmen; for Major C. Mackenzie”. Asiatick Researches: Or Transactions of the Society; Instituted In Bengal, For Enquiring Into The History And Antiquities, the Arts, Sciences, and Literature, of Asia, 9, 244-286. PDF. Retrieved from: https://archive.org/details/in.ernet.dli.2015.104510Chamber’s Twentieth Century Dictionary [The]. (1971). Bombay et al: Allied Publishers. Print.Chatterjee, Dilip Kumar. (1989). Cousins and Sri Aurobindo: A Study in Literary Influence, Journal of South Asian Literature, 24(1), 114-123. Retrieved from: http://www.jstor.org/ stable/40873985.Chattopadhyay, Dilip Kumar. (1988). A Study of the Works of James Henry Cousins (1873-1956) in the Light of the Theosophical Movement in India and the West. Unpublished PhD dissertation. Burdwan: The University of Burdwan. PDF. Retrieved from: http://ir.inflibnet. ac.in:8080/jspui/bitstream/10603/68500/9/09_chapter%205.pdf.Cobuild English Language Dictionary. (1989 [1987]). rpt. London and Glasgow. Collins Cobuild Advanced Illustrated Dictionary. (2010). rpt. Glasgow: Harper Collins. Print.Concise Oxford English Dictionary [The]. (1961 [1951]). H. W. Fowler and F. G. Fowler. (Eds.) Oxford: Clarendon Press. 4th ed.Cousins, James H. (1921). Modern English Poetry: Its Characteristics and Tendencies. Madras: Ganesh & Co. n. d., Preface is dated April, 1921. PDF. Retrieved from: http://hdl.handle.net/ 2027/uc1.$b683874---. (1919) New Ways in English Literature. Madras: Ganesh & Co. 2nd edition. PDF. Retrieved from: https://archive.org/details/in.ernet.dli.2015.31747---. (1918). The Renaissance in India. Madras: Madras: Ganesh & Co., n. d., Preface is dated June 1918. PDF. Retrieved from: https://archive.org/details/in.ernet.dli.2015.203914Das, Sisir Kumar. (1991). History of Indian Literature. Vol. 1. New Delhi: Sahitya Akademi.Encarta World English Dictionary. (1999). London: Bloomsbury.Gandhi, M K. (1938 [1909]). Hind Swaraj Tr. M K Gandhi. Ahmedabad: Navajivan Publishing House. PDF. Retrieved from: www.mkgandhi.org/ebks/hind_swaraj.pdf.Gokak, V K. (n.d.). English in India: Its Present and Future. Bombay et al: Asia Publishing House. PDF. Retrieved from: https://archive.org/details/in.ernet.dli.2015.460832Goodwin, Gwendoline (Ed.). (1927). Anthology of Modern Indian Poetry, London: John Murray. PDF. Retrieved from: https://archive.org/details/in.ernet.dli.2015.176578Guptara, Prabhu S. (1986). Review of Indian Literature in English, 1827-1979: A Guide to Information Sources. The Yearbook of English Studies, 16 (1986): 311–13. PDF. Retrieved from: https://www.jstor.org/stable/3507834Iyengar, K R Srinivasa. (1945). Indian Contribution to English Literature [The]. Bombay: Karnatak Publishing House. PDF. Retrieved from: https://archive.org/details/ indiancontributi030041mbp---. (2013 [1962]). Indian Writing in English. New Delhi: Sterling.---. (1943). Indo-Anglian Literature. Bombay: PEN & International Book House. PDF. Retrieved from: https://archive.org/details/IndoAnglianLiteratureLongman Dictionary of Contemporary English. (2003). Essex: Pearson.Lyall, Alfred Comyn. (1915). The Anglo-Indian Novelist. Studies in Literature and History. London: John Murray. PDF. Retrieved from: https://archive.org/details/in.ernet. dli.2015.94619Macaulay T. B. (1835). Minute on Indian Education dated the 2nd February 1835. HTML. Retrieved from: http://www.columbia.edu/itc/mealac/pritchett/00generallinks/macaulay/ txt_minute_education_1835.htmlMehrotra, Arvind Krishna. (2003). An Illustrated History of Indian Literature in English. Delhi: Permanent Black.---. (2003[1992]). The Oxford India Anthology of Twelve Modern Indian Poets. New Delhi: Oxford U P.Minocherhomji, Roshan Nadirsha. (1945). Indian Writers of Fiction in English. Bombay: U of Bombay.Modak, Cyril (Editor). (1938). The Indian Gateway to Poetry (Poetry in English), Calcutta: Longmans, Green. PDF. Retrieved from http://en.booksee.org/book/2266726Mohanty, Sachidananda. (2013). “An ‘Indo-Anglian’ Legacy”. The Hindu. July 20, 2013. Web. Retrieved from: http://www.thehindu.com/features/magazine/an-indoanglian-legacy/article 4927193.eceMukherjee, Sujit. (1968). Indo-English Literature: An Essay in Definition, Critical Essays on Indian Writing in English. Eds. M. K. Naik, G. S. Amur and S. K. Desai. Dharwad: Karnatak University.Naik, M K. (1989 [1982]). A History of Indian English Literature. New Delhi: Sahitya Akademi, rpt.New Shorter Oxford English Dictionary on Historical Principles [The], (1993). Ed. Lesley Brown, Vol. 1, Oxford: Clarendon Press.Naik, M K. (1989 [1982]). A History of Indian English Literature. New Delhi: Sahitya Akademi, rpt.Oaten, Edward Farley. (1953 [1916]). Anglo-Indian Literature. In: Cambridge History of English Literature, Vol. 14, (pp. 331-342). A C Award and A R Waller, (Eds). Rpt.---. (1908). A Sketch of Anglo-Indian Literature, London: Kegan Paul. PDF. Retrieved from: https://ia600303.us.archive.org/0/items/sketchofangloind00oateuoft/sketchofangloind00oateuoft.pdf)Advanced Learner’s Dictionary of Current English. (1979 [1974]). A. S. Hornby (Ed). : Oxford UP, 3rd ed.Oxford English Dictionary [The]. Vol. 7. (1991[1989]). J. A. Simpson and E. S. C. Weiner, (Eds.). Oxford: Clarendon Press, 2nd ed.Pai, Sajith. (2018). Indo-Anglians: The newest and fastest-growing caste in India. Web. Retrieved from: https://scroll.in/magazine/867130/indo-anglians-the-newest-and-fastest-growing-caste-in-indiaPandia, Mahendra Navansuklal. (1950). The Indo-Anglian Novels as a Social Document. Bombay: U Press.Payn, James. (1880). An Indo-Anglian Poet, The Gentleman’s Magazine, 246(1791):370-375. PDF. Retrieved from: https://archive.org/stream/gentlemansmagaz11unkngoog#page/ n382/mode/2up.---. (1880). An Indo-Anglian Poet, Littell’s Living Age (1844-1896), 145(1868): 49-52. PDF. Retrieved from: https://archive.org/stream/livingage18projgoog/livingage18projgoog_ djvu.txt.Rai, Saritha. (2012). India’s New ‘English Only’ Generation. Retrieved from: https://india.blogs.nytimes.com/2012/06/01/indias-new-english-only-generation/Raizada, Harish. (1978). The Lotus and the Rose: Indian Fiction in English (1850-1947). Aligarh: The Arts Faculty.Rajan, P K. (2006). Indian English literature: Changing traditions. Littcrit. 32(1-2), 11-23.Rao, Raja. (2005 [1938]). Kanthapura. New Delhi: Oxford UP.Rogobete, Daniela. (2015). Global versus Glocal Dimensions of the Post-1981 Indian English Novel. Portal Journal of Multidisciplinary International Studies, 12(1). Retrieved from: http://epress.lib.uts.edu.au/journals/index.php/portal/article/view/4378/4589.Rushdie, Salman & Elizabeth West. (Eds.) (1997). The Vintage Book of Indian Writing 1947 – 1997. London: Vintage.Sampson, George. (1959 [1941]). Concise Cambridge History of English Literature [The]. Cambridge: UP. Retrieved from: https://archive.org/details/in.ernet.dli.2015.18336.Sarma, Gobinda Prasad. (1990). Nationalism in Indo-Anglian Fiction. New Delhi: Sterling.Singh, Kh. Kunjo. (2002). The Fiction of Bhabani Bhattacharya. New Delhi: Atlantic Publishers and Distributors.Spivak, Gayatri Chakravorty. (2012). How to Read a ‘Culturally Different’ Book. An Aesthetic Education in the Era of Globalization, Cambridge, Mass: Harvard University Press.Sturgeon, Mary C. (1916). Studies of Contemporary Poets, London: George G Hard & Co., Retrieved from: https://archive.org/details/in.ernet.dli.2015.95728.Thomson, W S (Ed). (1876). Anglo-Indian Prize Poems, Native and English Writers, In: Commemoration of the Visit of His Royal Highness the Prince of Wales to India. London: Hamilton, Adams & Co., Retrieved from https://books.google.co.in/ books?id=QrwOAAAAQAAJWadia, A R. (1954). The Future of English. Bombay: Asia Publishing House.Wadia, B J. (1945). Foreword to K R Srinivasa Iyengar’s The Indian Contribution to English Literature. Bombay: Karnatak Publishing House. Retrieved from: https://archive.org/ details/indiancontributi030041mbpWebster's Encyclopedic Unabridged Dictionary of the English Language. (1989). New York: Portland House.Yule, H. and A C Burnell. (1903). Hobson-Jobson: A Glossary of Colloquial Anglo-Indian Words and Phrases, and of Kindred Terms, Etymological, Historical, Geographical and Discursive. W. Crooke, Ed. London: J. Murray. Retrieved from: https://archive.org/ details/hobsonjobsonagl00croogoogSourceswww.amazon.com/Indo-Anglian-Literature-Edward-Charles-Buck/dp/1358184496www.archive.org/stream/livingage18projgoog/livingage18projgoog_djvu.txtwww.catalog.hathitrust.org/Record/001903204?type%5B%5D=all&lookfor%5B%5D=indo%20anglian&ft=www.en.wikipedia.org/wiki/B.L._Indo_Anglian_Public_School,_Aurangabadwww.everyculture.com/South-Asia/Anglo-Indian.htmlwww.solo.bodleian.ox.ac.uk/primo_library/libweb/action/search.do?fn=search&ct=search&initialSearch=true&mode=Basic&tab=local&indx=1&dum=true&srt=rank&vid=OXVU1&frbg=&tb=t&vl%28freeText0%29=Indo-Anglian+Literature+&scp.scps=scope%3A%28OX%29&vl% 28516065169UI1%29=all_items&vl%281UIStartWith0%29=contains&vl%28254947567UI0%29=any&vl%28254947567UI0%29=title&vl%28254947567UI0%29=anywww.worldcat.org/title/indo-anglian-literature/oclc/30452040